2022
DOI: 10.3390/healthcare10071270
|View full text |Cite
|
Sign up to set email alerts
|

HPV Self-Sampling for Cervical Cancer Screening among Women Living with HIV in Low- and Middle-Income Countries: What Do We Know and What Can Be Done?

Abstract: Introduction. Self-sampling has the potential to increase cervical cancer (CC) screening among women with HIV in low- and middle-income countries (LMICs). However, our understanding of how HPV self-collection studies have been conducted in women with HIV is limited. The purpose of this scoping review was to examine the extent to which the HPV self-sampling has been applied among women with HIV in LMICs. Method: We conducted multiple searches in several databases for articles published between 2000 and January … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
2
4
0
Order By: Relevance
“…Another strong finding was that the women reported a positive experience with collecting self-sampling. This finding is supported by a recent meta-analysis of 37 studies among 18,516 women from 24 countries across five continents and a scoping review [54] that indicated women have a strong acceptance and preference for self-sampling over clinician sampling [36]. The women in our study implied that self-sampling could help alleviate the economic burden and increase the accessibility of cervical cancer screening for low-income women.…”
Section: Discussionsupporting
confidence: 81%
“…Another strong finding was that the women reported a positive experience with collecting self-sampling. This finding is supported by a recent meta-analysis of 37 studies among 18,516 women from 24 countries across five continents and a scoping review [54] that indicated women have a strong acceptance and preference for self-sampling over clinician sampling [36]. The women in our study implied that self-sampling could help alleviate the economic burden and increase the accessibility of cervical cancer screening for low-income women.…”
Section: Discussionsupporting
confidence: 81%
“…Another strong finding was that the women reported a positive experience with collecting self-sampling. This finding is supported by a recent meta-analysis of 37 studies among 18,516 women from 24 countries across five continents and a scoping review [57] that indicated women have a strong acceptance and preference for self-sampling over clinician sampling [37]. The women in our study implied that self-sampling could help alleviate the economic burden and increase the accessibility of cervical cancer screening for low-income women.…”
Section: Discussionsupporting
confidence: 81%
“…With similar laboratory performance of self-sampling procedures to clinician-performed sampling, high participation and reported satisfaction rates for the individuals, there is clear potential for increasing overall cervical cancer screening uptake with VSS in this population and maximizing efficiency and cost-effectiveness, essentially implementing the same networks and infrastructures, with comparatively lower additional costs. This gains additional importance, given the contribution of underserved patients living with HIV in the global burden of cervical precancer and cancer morbidity and mortality [ 42 , 43 ].…”
Section: Aspects Of Vaginal Self-sampling Implementationmentioning
confidence: 99%